The law relating to domestic banking : banking law volume 1 - Penn, G. A.; Shea, A. M.; Arora, Anu. (London : Sweet & Maxwell, 1987)
This edition of Domestic Banking presents a survey of the law of banking as it relates to the banking community today.
Includes bibliographical references and index.
ucj 17/01/2019
Loans
Keywords: Banking law